Braiding kinetics and spectroscopy in photo-catalysis: the spectro-kinetic approach. (5th December 2018) - Muñoz-Batista, Mario J.; Ballari, María M.; Kubacka, Anna; Alfano, Orlando M.; Fernández-García, Marcos
Abstract : A guidebook and reference for the interpretation of photocatalytic performance from the combined analysis of kinetic and spectroscopic data. Abstract : The combination of kinetic and spectroscopic tools has become a key scientific methodology for the understanding of catalytic behavior but its application in photocatalysis has inherent difficulties due to the nature of the energy source of the reaction. This review article provides an overview of its use by, first, presenting mechanistically derived kinetic formulations and spectroscopic data handling methods including intrinsic expressions for light and, second, highlighting representative examples of application. To do it we consider universal catalytic systems, particularly (although not exclusively) titania-based materials, and the most frequent hole and/or electron triggered reaction schemes. This review also provides a general framework to pave the way for the future progress of the spectro-kinetic approach in the photocatalysis area.